Biological Properties and Medical Applications of Carbonate Apatite: A Systematic Review - Ralitsa Yotsova; Stefan Peev (MDPI AG, 2024)
Bone defects represent an everyday challenge for clinicians who work in the fields of orthopedic surgery, maxillofacial and oral surgery, otorhinolaryngology, and dental implantology. Various bone substitutes have been developed and utilized, according to the needs of bone reconstructive surgery. Carbonate apatite has gained popularity in recent years, due to its excellent tissue behavior and osteoconductive potential. This systematic review aims to evaluate the role of carbonate apatite in bone reconstructive surgery and tissue engineering, analyze its advantages and limitations, and suggest further directions for research and development. The Web of Science, PubMed, and Scopus electronic databases were searched for relevant review articles, published from January 2014 to 21 July 2023. The study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eighteen studies were included in the present review. The biological properties and medical applications of carbonate apatite (CO3Ap) are discussed and evaluated. The majority of articles demonstrated that CO3Ap has excellent biocompatibility, resorbability, and osteoconductivity. Furthermore, it resembles bone tissue and causes minimal immunological reactions. Therefore, it may be successfully utilized in various medical applications, such as bone substitution, scaffolding, implant coating, drug delivery, and tissue engineering.